ASIAN EXPERIENCE OF INCLUSIVE EDUCATION IMPLEMENTATION - Голуб, Руслана; Ферт, Ольга (SWorldJournal, 2022)
The article examines the experience and historical aspects of the implementation of inclusive education in Asia, which is extremely useful for effective reform of inclusive education policy in Ukraine. Today, humanity is turning to a new paradigm of worl